Emission examination of lemongrass biodiesel and novel nanoparticle blends in research diesel engine. Issue 1 (31st December 2022) - Ashraff Ali, K. S.; Ramakrishnan, C.; Parthasarathi, R.; Inigo, C.; Vinayagam, Mohanavel
Abstract : This work investigates the impact on adding novel graphene oxide (GO) nanoparticle on Lemongrass biodiesel (LGBD) and views its effect on engine emissions. LGBD is produced by conventional transesterification which requires raw oil, alcohol (methanol) and catalysts (KOH). GO nanoparticle is dispersed into LGBD at 100 and 200 ppm and termed as LGBD100GO and LGBD200GO, respectively. Emissions experiments were conducted on a diesel engine using LGBD, LGBD100GO and LGBD200GO at the same conditions. Experimental results show that the LGBD100GO and LGBD200GO and have lesser HC (7 and 13 ppm), CO (0.02 and 0.03%) and NO (134 and 185 ppm) emissions than LGBD due to the improved catalytic activity and thermal conductivity of GO nanoparticle.